Pengelolaan Keuangan Desa Pada Struktur Perangkat Desa Tanah Merah Torjun-Sampang - Mychelia Champaca; Moch Nurhidayat (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Government regulations, that is, Law Number 60 of 2014, are the basis for central government policy in allocating budgets from the APBN for village funds, or Dana Desa (DD). Through the disbursement of this budget, the government seeks to increase economic equality in remote villages. In order for the goal of DD allocation to facilitate village programs to be achieved, intense outreach from the government and educational institutions is necessary so as to minimize leakage in the form of acts of corruption that impede the running of village programs. A village program that is funded and running well will form a developed and self-sufficient village so that it can create new jobs for the surrounding community. To answer the educational role of educational institutions as a companion for channeling DD to productive community activities, the Faculty of Economics, Universitas Brawijaya, through a team of lecturers and students, carries out community service activities that carry the urgency of village financial literacy socialization. The location for this community service activity was in Tanah Merah Village, Torjun-Sampang, taking into account that during the year the village head was involved in the Village Fund corruption case. Referring to the motivation for holding this activity, the community service activities are aimed at providing education regarding the financial management of the village fund for village government officials. This community service activity is carried out using the hybrid method, that is, the delivery of material by presenters both offline and online. Furthermore, as feedback to determine the effectiveness of the implementation of activities, a questionnaire was given to the participants. Participants in this community service activity are village officials and PLT village heads. The results of the implementation of this community service activity can be concluded: that the management of village finances is only known and carried out by the Village Head and Head of Village Finance; most of the activity participants did not understand the assets and programs owned by the village government; and that village financial education activities have never been given before, so the implementation of these training activities provides insight into the urgency of transparent financial management for the implementation of village program formulations that are effective and in accordance with what the community needs.